The role of protease-activated receptor 1 signaling in CD8 T cell effector functions - Hui Chen (Elsevier, 2021)
Summary: CD8 T cells are essential for adaptive immunity against viral infections. Protease activated receptor 1 (PAR1) is expressed by CD8 T cells; however, its role in T cell effector function is not well defined. Here we show that in human CD8 T cells, PAR1 stimulation accelerates calcium mobilization. Furthermore, PAR1 is involved in cytotoxic T cell function by facilitating granule trafficking via actin polymerization and repositioning of the microtubule organizing center (MTOC) toward the immunological synapse. In vivo, PAR1−/− mice have reduced cytokine-producing T cells in response to a lymphocytic choriomeningitis virus (LCMV) infection and fail to efficiently control the virus. Specific deletion of PAR1 in LCMV GP33-specific CD8 T cells results in reduced expansion and diminished effector function. These data demonstrate that PAR1 plays a role in T cell activation and function, and this pathway could represent a new therapeutic strategy to modulate CD8 T cell effector function.